First report of the wages and salaries review commission 1970 - Federal republic of Nigeria (Lagos Federal ministry of information printing division, 1970)
This book is a report of the 1970 commission set up to examine existing wages and salaries and to examine staff remuneration and harmonization in line with the reviews.
asm; 06/03/19
Loans
Keywords: Wages; Nigeria